2011
DOI: 10.1007/s11199-011-9962-z
|View full text |Cite
|
Sign up to set email alerts
|

Racial Identity and Gender as Moderators of the Relationship Between Body Image and Self-esteem for African Americans

Abstract: This study explored whether multiple dimensions of racial identity and gender moderated the relationship between body dissatisfaction and self-esteem for African American men and women (N=425) using an intersectional approach. Centrality (strength of identification with racial group), private regard (positive feelings about racial group), public regard (positive feelings others have about racial group), and gender moderated the relationship between body dissatisfaction and self-esteem for a sample of men (n=10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 54 publications
2
68
0
Order By: Relevance
“…This may be especially true for African American women who are challenged to maintain a healthy sense of self within a culture that views them as deviant from the thin and often White gendered body ideal (Henrickson et al 2010;Hesse-Biber 2004;Zhang et al 2009). In this issue, Oney et al (2011) explored whether gender and multiple dimensions of racial identity moderated the link between body dissatisfaction and self-esteem for African American women and men from three regions of the U.S. They found that the negative relationship between body dissatisfaction and self-esteem was stronger for women than for men, supporting assertions that U.S. women, regardless of ethnicity, are socialized to equate their overall self-worth with their appearance (Clark 2009;Fredrickson and Roberts 1997).…”
Section: Stream Two: Gendered Body Constrictionsmentioning
confidence: 89%
See 4 more Smart Citations
“…This may be especially true for African American women who are challenged to maintain a healthy sense of self within a culture that views them as deviant from the thin and often White gendered body ideal (Henrickson et al 2010;Hesse-Biber 2004;Zhang et al 2009). In this issue, Oney et al (2011) explored whether gender and multiple dimensions of racial identity moderated the link between body dissatisfaction and self-esteem for African American women and men from three regions of the U.S. They found that the negative relationship between body dissatisfaction and self-esteem was stronger for women than for men, supporting assertions that U.S. women, regardless of ethnicity, are socialized to equate their overall self-worth with their appearance (Clark 2009;Fredrickson and Roberts 1997).…”
Section: Stream Two: Gendered Body Constrictionsmentioning
confidence: 89%
“…Importantly, Oney et al (2011) found that racial centrality (the extent to which being African American is an important aspect of identity) buffered the link between body dissatisfaction and self-esteem, such that body dissatisfaction was unrelated to self-esteem for African Americans who were high in racial centrality but negatively related to self-esteem for those low in racial centrality. Public regard (perceptions that other racial groups have positive feelings toward African Americans) buffered this relationship in the same fashion as racial centrality.…”
Section: Stream Two: Gendered Body Constrictionsmentioning
confidence: 95%
See 3 more Smart Citations